(untitled) (Journal of Advanced Veterinary and Animal Research, 2023)
Objective: This research assesses whether probiotics could enhance growth performance and improve nutrient digestibility in birds fed with low-protein diets. Materials and Methods: A total of 250 1-day-old ROSS chicks were used in a completely randomized design consisting of 5 treatments with 5 replicates and 10 birds for each replicate. The experimental diets were as follows: basal diet containing 100% crude protein (CP) according to Nutrition Research Council recommendation (control diet); basal diet containing CP 10% less than the control diet low protein (LP); LP with addition of probiotic by 50 mg/kg diet (LP + P1); LP with addition of probiotics by 100 mg/kg diet (LP + P2); LP with an addition of probiotics by 150 mg/ kg diet (LP + P3). Results: Broilers fed with the control, LP + P2, and LP + P3 diets had greater body weight and weight gain than broilers fed with the LP during starter, finisher, and total periods (p < 0.01). The feed conversion ratio was the best (p < 0.01) in the control and LP + P3 treatments compared with the LP and LP + P1 treatments throughout the experiment. The European production efficiency factor was the lowest in the LP treatment compared with other treatments from 1 to 42 days. Protein efficiency ratio and protein retention were both higher in birds fed with the LP + P2 and LP + P3 diets compared to birds given the control and LP diets (p < 0.01). Conclusion: Adding probiotics to the diet remarkably improved the productive performance and nutrient digestibility of broiler-fed low-protein diets. J. Adv. Vet. Anim. Res., 10(3): 395–402, September 2023 http://doi.org/10.5455/javar.2023.j692